Høyoppløselig rekonstruksjon av brefluktuasjoner på Fastdalstindbreen gjennom holosen. En studie basert på kvartærgeologisk kartlegging og analyse av innsjøsedimenter fra Elvejordsvatnet, Lyngen, Nord-Norge - Rinnan, Arild Sunde (The University of Bergen, 2012)
Fastdalstindbreen is a ~0, 16 km2 lager cirque glacier below the mountain Fastdalstind in Lyngen, Northern Norway. Cirque glaciers can be sensitive indicators of change in temperature, precipitation or wind direction. Reconstructing past activity can therefore give records of past climatic change. The aim of this thesis is to make a high- resolution glacier reconstruction of the Holocene fluctuation of Fastdalstindbreen, and the winter precipitation on the Lyngen Peninsula, northern Norway. The Lyngen peninsula has a maritime climate, and the glaciers located there is sensitive to changes in the winter precipitation and summer temperatures. By comparing the reconstruction from Lyngen with other climate reconstructions in both the Northern and Southern hemispheres, it was possible to assess how the small cirque glacier on Fastdalstind responds to changes in regional and global climate conditions. Based on mapping of the surficial deposits and analyses of sediment cores, an equilibrium line altitude curve (ELA) has been constructed. Pollen samples from the same cores were used to reconstruct a record of July temperatures. Avalanche and glacial deposits in the field area where mapped, and sediment samples were retrieved from the catchment area. One marginal moraine was registered in front of the Fastdalstind glacier. Two piston-cores and one HTH-core were retrieved from Elvejordsvatnet (62 m.a.s.l) in March 2011. The cores underwent laboratory analyses including X-ray fluorescents (XRF), loss-on-ignition (LOI), dry bulk density (DBD), grain size distribution and magnetic susceptibility (MS). The sediment samples from the catchment were analysed with XRF and MS. They were later used as a provenance for glacial sediments. With 22 lead- and radiocarbon dates from the sediment cores, an age model spanning the last 7000 years BP was constructed. Based on known ELA positions of the glacier and sediment parameters reflecting glacial activity, a regression model was made showing the ELA fluctuations of Fastdalstindbreen ...